Combined in Vitro and in Silico Studies for the Anticholinesterase Activity and Pharmacokinetics of Coumarinyl Thiazoles and Oxadiazoles - Ibrar, Aliya; Khan, Ajmal; Ali, Majid; Sarwar, Rizwana; Mehsud, Saifullah; Farooq, Umar; Halimi, Syed M. A.; Khan, Imtiaz; Al-Harrasi, Ahmed (Frontiers in Chemistry, 2018)
In a continuation of our previous work for the exploration of novel enzyme inhibitors, two new coumarin-thiazole 6(a–o) and coumarin-oxadiazole 11(a–h) hybrids have been designed and synthesized. All the compounds were characterized by 1H- and 13C-NMR spectroscopy and elemental analysis. New hybrid analogues were evaluated against acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) in order to know their potential for the prevention of Alzheimer’s disease (AD). In coumarinyl thiazole series, compound 6b was found as the most active member against AChE having IC50 value of 0.87 ± 0.09 µM, while the compound 6j revealed the same efficacy against BuChE with an IC50 value of 11.01 ± 3.37 µM. In case of coumarinyl oxadiazole series, 11a was turned out to be the lead candidate against AChE with an IC50 value of 6.07 ± 0.23 µM, whereas compound 11e was found significantly active against BuChE with an IC50 value of 0.15 ± 0.09 µM. To realize the binding interaction of these compounds with AChE and BuChE, the molecular docking studies were performed. Compounds from coumarinyl thiazole series with potent AChE activity (6b, 6h, 6i and 6k) were found to interact with AChE in the active site with MOE score of ‒10.19, ‒9.97, ‒9.68, and ‒11.03 Kcal.mol‒1, respectively. The major interactions include hydrogen bonding, π-π stacking with aromatic residues, and interaction through water bridging. The docking studies of coumarinyl oxadiazole derivatives 11(a-h) suggested that the compounds with high anti-butyrylcholinesterase activity (11e, 11a and 11b) provided MOE score of ‒9.9, ‒7.4 and ‒8.2 Kcal.mol‒1 respectively, with the active site of BuChE building π-π stacking with Trp82 and water bridged interaction.